Community Perceptions on Motor Vehicle Loss Services by Central Bengkulu District Police - Melati Putri Komala; Sapta Sari; Bayu Risdiyanto (Jurnal Multidisiplin Dehasen (MUDE), 2023)
The purpose of this research is to find out the society perception on motor vehicle loss services at Police Department of Center of Bengkulu. Data are obtained by implementing several data collection techniques such as observation, interview, documentation and literature review. Data then analyzed by using perception pattern theory by Bitner according to 3 main elements such as stimuli, organism and response. The result of the research shows that 1) Central of Bengkulu police station has become good information source, it gives good information about report. Society think that the officer has served people when they want to make a call by giving detail information so society can understand the steps and administrative steps in making a report. 3) society perception is different, some people said that the loss report service has good while the other said the service is slow. It can be found from the data from investigation of motor vehicle loss, from 2022-2023, from 5 loss motorcycles, only 1 which can be found. Because of that reason, it can affect society’s perception. From the writer’s observation, the process is slow because it needs to passed through of several investigation. The problem from police department is because there is no CCTV at the loss area and the vehicle has no equipment. When the motorcycle is found, the police department is not giving it back to its owner but has to complete the council process to find out the stealer network at the center of Bengkulu.